Nutraceuticals Unveiled: Exploring the Science, Benefits, and Future of Functional Food - Prakhar Bajpayee; Akanksha Dwivedi; G. N. Darwhekar (International Journal of Nutritions, 2025)
The rapidly developing subject of nutraceuticals is critically examined in this review, with a focus on its scientific basis, proven health advantages, and possible future applications in the functional food industry. Key bioactive ingredients that contribute to the therapeutics effectiveness of functional foods, including flavonoids, polyphenols, carotenoids, probiotics, and essential fatty acids, have been identified and characterized as a result of recent developments in nutritional science. Both experimental and clinical data have demonstrated the compound’s potential biological activity, which includes ant oxidative, anti-inflammatory, cardioprotective and neuroprotective properties. The article examines the manner, in which these useful elements interact with physiological systems to affect immunological responses, metabolic control and cellular signaling pathways. Additionally, it emphasizes their contribution to the prevention and supplemental treatment of non-communicable illnesses, such as diabetes, heart disease, and cognitive decline. With a focus on developments in food processing and formulation technologies, the study also addresses aspects that affect these compounds’ bioavailability and effectiveness. The review highlights important themes that will influence this industry going ahead, such as sustainable functional food production. AI-enables dietary advice, microbiome-targeted therapies, and precision nutrition. It is anticipated that consumer desire for plant-based, natural, and clean-label functional goods will spur further development and incorporation of nutraceuticals into conventional health approaches. This review seeks to give academics, clinicians, and industry stakeholders a thorough overview by combining current knowledge and future directions. It emphasizes the critical role nutraceuticals play in contemporary health promotion and the changing paradigm of functional food science.
Keywords: Bioactive compounds; Functional Foods; antioxidant; nutraceuticals; therapeutic